Comparison of nisin and monensin effects on ciliate and selected bacterial populations in artificial rumen - Kisidayová, S; Lauková, A; Jalc, D (Folia microbiologica, 2009)
The effect of daily supplementation of nisin (2 mg/L), monensin (5.88 mg/L) and nisin and monensin (2 + 5.88 mg/L) on ovine ruminal ciliates and bacteria was investigated using the artificial rumen RUSITEC. Major groups in RUSITEC were Entodinium spp. and Dasytricha ruminantium. The supplementation of nisin significantly increased the population of both major ciliate groups. The supplementation of monensin significantly decreased the population of both groups. The combined effect of nisin and monensin was similar to the effect of monensin. Monensin had strong antiprotozoic effects in contrast to the stimulatory effects of nisin. D. ruminantium followed by Entodinium spp. appeared more resistant to tested compounds than other rumen ciliates. Tested additives did not significantly influence the presence and growth of amylolytic streptococci and enterococci but nisin showed a tendency to decreasing the concentration of Escherichia coli and lactobacilli.
Keywords: nisin; dezinficiencia; Disinfectants; Monensin; Nisin; Diet; dieta; teoretické modely; zvířata; Rumen; Sheep; monensin; Eukaryota; ovce; Bacteria; Models, Theoretical; bachor; Animals